Pengaruh Pemberian Penguatan Guru Pendidikan Agama Kristen dan Guru Bimbingan Konseling Terhadap Hasil Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas IX SMP Negeri 1 Palipi Tahun Pembelajaran 2023/2024 - Sari Mutiara Sinaga; Dapot Damanik; Wilson Simajuntak; Binur Panjaitan; Hisardo Sitorus (Jurnal Pendidikan Agama dan Teologi, 2024)
The objectives of this study are 1) to determine the effect of giving reinforcement by Christian Religious Education Teachers on the learning outcomes of Christian Religious Education and Budi Pekerti Class IX Students of SMP N 1 Palipi in the 2023/2024 Learning Year; 2) to determine the effect of giving reinforcement by Counseling Guidance Teachers on the learning outcomes of Christian Religious Education and Budi Pekerti Class IX Students of SMP N 1 Palipi in the 2023/2024 Learning Year; 3) to determine the effect of giving reinforcement by Christian Religious Education Teachers and Counseling Guidance Teachers together on the Learning Outcomes of Christian Religious Education and Budi Pekerti Class IX Students of SMP N 1 Palipi in the 2023/2024 Learning Year. The method used in this research is inferential quantitative method with expo-facto correlation model. The population is all ninth grade students of SMP Negeri 1 Palipi in the 2023/2024 Learning Year, totaling 160 people and a sample of 40 people was determined using random sampling technique. Data were collected with a closed questionnaire of 32 items. The results of data analysis show that: 1) the value of F count> F table between the Strengthening of Christian Religious Education Teachers on Student Learning Outcomes of Christian Religious Education and Budi Pekerti Students is 14.849> 3.23, thus it is known that there is an influence between the Strengthening of Christian Religious Education Teachers on Student Learning Outcomes of Christian Religious Education and Budi Pekerti Students, namely 28, 1%, 2) the value of F count> F table between the Giving of Strengthening the Counseling Guidance Teacher on the Learning Outcomes of Christian Religious Education and Budi Pekerti Students, namely 14.651> 3.23, thus it is known that there is an influence of the Giving of Strengthening the Counseling Guidance Teacher on the Learning Outcomes of Christian Religious Education and Budi Pekerti Students, namely 27, 8%, 3) the value of F count> F table between the Strengthening of Christian Religious Education Teachers and the Strengthening of Counseling Guidance Teachers on the Learning Outcomes of Christian Religious Education and Budi Pekerti Students, namely 10.569> 3.23, thus it is known that there is an influence of the Strengthening of Christian Religious Education Teachers and the Strengthening of Counseling Guidance Teachers on the Learning Outcomes of Christian Religious Education and Budi Pekerti Students in Class IX SMP N 1 Palipi Learning Year 2023/2024 which is 36.4%, thus Ha is accepted and H0 is rejected.